INTRAVENOUS VERSUS INTRANASAL DEXMEDETOMIDINE: A COMPARATIVE ANALYSIS OF HEMODYNAMIC RESPONSES DURING LARYNGOSCOPY AND ENDOTRACHEAL INTUBATION - SARA MARY THOMAS; PARAS ANAND; DUSHYANT BHARATBHAI CHAVDA; KALPESH PATIL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Laryngoscopy and intubation causes a profound sympathetic response, causing significant increase in heart rate (HR) and blood pressure, potentially leading to complications like laryngospasm and bronchospasm, requiring close monitoring and expert anesthesia care. This study evaluated intranasal and intravenous effectiveness of dexmedetomidine in mitigating adverse hemodynamic consequences to laryngoscopy and intubation, aiming to discern the optimal route for hemodynamic stability. Methods: This double-blinded, randomized study involved 72 adults (18–60 years, American Society of Anesthesiologists I/II) undergoing various surgeries requiring general anesthesia and endotracheal intubation. Group DIV received Inj. Dexmedetomidine 1 μg/kg intravenously as an infusion in 100 mL Normal Saline over 10 min, 40 min before induction of general anesthesia. Group DIN received Inj. Dexmedetomidine 2 μg/kg (1 μg/kg in each nostril) intranasally through atomizer 40 min before induction of general anesthesia. The study’s primary objective was to optimize dexmedetomidine’s route and dosage for minimizing laryngoscopy’s stress response. Secondary outcomes included assessing incidence of any adverse event. Results: Both study groups showed similar demographics, study duration, and baseline hemodynamics. Hemodynamic parameters decreased significantly 30–40 min post-administration of study drug and after induction (p<0.05). Laryngoscopy and intubation increased HR and mean arterial pressure (MAP) where Group DIN HR (98.86±17.16 bpm), MAP (108.5±15.69 mmHg) showed more increase than Group DIV HR (88.89±9.23 bpm) and MAP (102.36±9.06 mmHg). Group DIV showed greater attenuation of hemodynamic parameters at 1, 3, and 5 min post-laryngoscopy (p<0.05). Conclusion: Intravenous dexmedetomidine 1 μg/kg is more effective than intranasal dexmedetomidine 2 μg/kg in attenuating the hemodynamic stress response to laryngoscopy and intubation.